Helper T cell plasticity: Impact of Extrinsic and Intrinsic Signals On Transcriptomes and Epigenomes - Bonelli, Michael (2014)
CD4(+) helper T cells are crucial for autoimmune and infectious diseases; however, the recognition of the many, diverse fates available continues unabated. Precisely what controls specification of helper T cells and preserves phenotypic commitment is currently intensively investigated. In this review, we will discuss the major factors that impact helper T cell fate choice, ranging from cytokines and the microbiome to metabolic control and epigenetic regulation. We will also discuss the technological advances along with the attendant challenges presented by “big data”, which allow the understanding of these processes on comprehensive scales.